PENGARUH PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Desy Ratna Sari; Asrinan; Asdar Dollo (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2025)
This study aims to evaluate the effectiveness of the Problem-Based Learning (PBL) model in improving the mathematical problem-solving abilities of students in the Smart Class Cerdas.1 at SMA Negeri 3 Parepare. The type of research used is quasi-experimental (pre-experimental) with a One Group Pretest-Posttest design. The research sample consisted of 29 students selected using cluster random sampling technique. Data were collected through observation sheets and a test instrument for problem-solving ability in the form of 3 essay questions based on Polya's indicators, then analyzed using descriptive and inferential statistics. The results showed a significant improvement, where the students' average score increased from 62.00 in the pretest to 86.17 in the posttest. This proves that the PBL model is effective in improving students' mathematical problem-solving abilities. The implication of this research indicates that the Problem-Based Learning model can be used as an effective alternative teaching strategy for educators to encourage students' critical and systematic thinking skills in mathematics subjects.